Efectos del tratamiento contable del parque automotor del GAD municipal cantón “Santa Rosa”, periodo 2017. - Becerra Granda, Robert Yazmanti (My University, 2019)
Public entities or the public sector are subject to the provisions established by the state, whose purpose is to control, maintain, preserve and make good use of the assets available to each public entity, according to their needs to be met by society. The objective of this research work is "Analyze the accounting effects through the execution of accounting regulations of the public sector, which are applied to control the automotive park of the Municipal Gad of Santa Rosa, period 2017; its specific objectives that contribute to the achievement of the general objective: a) to identify the accounting accounts applied to the vehicles of the Municipal Gad of Santa Rosa corresponding to the period 2017; b) Analyze the financial statements based on the accounting regulations of the public sector in the Municipal GAD of Santa Rosa for the period 2017; c) Verify the application of the accounting standards for the items that correspond to the GAD automotive fleet of Santa Rosa. To achieve the proposed objectives, the research work consists of four chapters. Chapter I deals with the generalities of the object of study; the research developed is carried out in the GAD Municipal del Cantón Santa Rosa; entity of the state that by means of the administration of own resources (collections of properties and taxes) as well as those destined by budget items (state budget); These resources, as they belong to the state, must be administered in order to satisfy the needs of the 14 parishes of the Santa Rosa Canton, the goods acquired to be used for the fulfillment of their responsibilities according to their competences, they must control them through accounting regulations that the government stipulates necessary for its control. Chapter II deals with the theoretical-epistemological foundation of the object of study; It deals in this section about when the Municipality of the Santa Rosa Canton was created, how it is integrated, the competencies that it has as an entity of the state as legal aspects of it. As the subject of the study deals with the accounting management of fixed assets in a specific way, the automotive fleet owned by the GAD Municipal del Cantón Santa Rosa, if the entity applies these accounting rules for the control of its fixed assets, considered in the Catalog of Accounting Accounts as part of the Property, Plant and Equipment; regulations that are issued by the Ministry of Economy and Finance, in addition to research contributions made by different authors on this subject considered important for companies. In the third Chapter the methodological process is developed, the descriptive method accompanied by bibliographic research, helped to identify how the assets are registered in their accounting accounts and compare them with what is established in the Governmental Accounting Standard of the Public Sector as well as what is stipulated in the catalog of accounts to make the accounting records of the goods (vehicles) established in the NCGSP. With the support of observation sheets and the interview, it was possible to identify in the table of accumulated depreciation that there are still assets recorded as lost and others that are obsolete and that they planned to write off. Chapter IV, makes reference to the results that the investigation throws, is that the entities of the public sector must be governed to the established thing in the Regulation of Government Accounting of the Public Sector and the catalog of Accounts to realize his accounting registers; the stock in books or tables must reflect the values with which the assets were registered and in the case of the existence of assets that have completed their accounting cycle or that in one way or another is due to obsolescence and considerable damage to the asset, be given low both in books and in the depreciation table, considering that it must be recorded that said asset is no longer part of its assets; whose means of evidence or proof of the loss is by issuance of invoice for sale either as scrap or as stipulated in such sale or also by a notary where it is testified that said good is being written off and that it will not be taken into account within of your accounting records. As a recommendation, it is proposed that procedures be issued for the accounting records, since these positions are for removal, whoever assumed the position reviews said documentation on how those records should be made and on the basis of which regulations the entity is governed.
Las entidades públicas o el sector público, están sometidas a las disposiciones establecidas por el estado, cuya finalidad es el controlar, mantener, preservar y dar buen uso a los bienes con los que disponga cada entidad pública, según sus necesidades a satisfacer de la sociedad. El objetivo del presente trabajo de investigación es “Analizar los efectos contables mediante la ejecución de normativas contables del sector público, que se aplican para controlar el parque automotor del Gad Municipal de Santa Rosa, periodo 2017; sus objetivos específicos que contribuyen al logro del objetivo general: a) identificar las cuentas contables aplicadas a los vehículos del Gad Municipal de Santa Rosa correspondiente al periodo 2017; b) Analizar los estados financieros en base a la normativa contable del sector público en el GAD Municipal de Santa Rosa al periodo 2017; c) Verificar la aplicación de las normas contables para los rubros que corresponden al parque automotor del GAD de Santa Rosa. Para alcanzar los objetivos propuestos, el trabajo de investigación se compone de cuatro capítulos. El capítulo I, trata sobre las generalidades del objeto de estudio; la investigación desarrollada es realizada en el GAD Municipal del Cantón Santa Rosa; entidad del estado que mediante la administración de recursos propios (cobros de predios e impuestos) como también los destinados por partidas presupuestarias (presupuesto del estado); estos recursos como son del estado los debe administrar con la finalidad de satisfacer las necesidades de las 14 parroquias con las que cuenta el Cantón Santa Rosa, los bienes adquiridos para ser utilizados para el cumplimiento de sus responsabilidades de acuerdo a sus competencias, las deben controlar mediante normativas contables que el gobierno estipule necesario para su control. El capítulo II, trata sobre la fundamentación teórico-epistemológico del objeto de estudio; trata en este apartado sobre cuando fue creada la Municipalidad del Cantón Santa Rosa, como está integrada, las competencias que posee como entidad del estado como aspectos legales del mismo. Como el tema de estudio trata sobre el manejo contable de los activos fijos de manera especificas el parque automotor que posee el GAD Municipal del Cantón Santa Rosa, si la entidad aplica dichas normas contables para el control de sus activos fijos, considerados en el Catálogo de Cuentas Contables como parte de la Propiedad, Planta y Equipos; normativas que son emitidas por el Ministerio de Economía y Finanzas, además de aportes de investigaciones realizadas por diferentes autores sobre este tema considerado como importante para las empresas. En el tercer Capítulo se desarrolla el proceso metodológico, el método descriptivo acompañado de investigaciones bibliográficas, ayudaron a identificar como se encuentran registrados los bienes en sus cuentas contables y compararlas con lo establecido en la Norma de Contabilidad Gubernamental del Sector Público como también lo estipulado en el catálogo de cuentas para realizar los registros contables de los bienes (vehículos) establecidos en la NCGSP. Con el apoyo de fichas de observación y la entrevista, se pudo identificar en la tabla de depreciación acumulada que aún hay activos registrados estando perdidos y otros que estan obsoletos y que planeaban dar de baja. El Capítulo IV, hace referencia a los resultados que arroja la investigación, es que las entidades del sector público deben regirse a lo establecido en la Norma de Contabilidad Gubernamental del Sector Público y el catálogo de Cuentas para realizar sus registros contables; las existencias en libros o tablas deben reflejar los valores con los cuales fueron registrados los bienes y en el caso de la existencia de activos que hayan cumplido su ciclo contable o que de una u otra manera sea por obsolescencia y daño considerable del bien, sea dado de baja tanto en libros como en la tabla de depreciación, considerando que se debe dejar constancia que dicho bien ya no este formando parte de sus activos; cuyo medio de evidencia o constancia de la baja es mediante emisión de factura por venta sea como chatarra o como se estipule en dicha venta o también mediante un notario donde se testique que dicho bien se está dando de baja y que no será tomado en cuenta dentro de sus registros contables. Como recomendación se propone que se emitan procedimientos para realizar los registros contables, debido a que dichos puesto son de remoción, quien asumiera el cargo revise dicha documentación de cómo se deben realizar dichos registros y en base a que normativas se rige la entidad.
Keywords: REGISTRO CONTABLE; NORMA DE CONTABILIDAD GUBERNAMENTAL DEL SECTOR PÚBLICO; PARQUE AUTOMOTOR; DEPRECIACIÓN ACUMULADA